Managing training in ISO 9002 : a training need analysis of officers in direct access, a division of Southern Bank Berhad - Azizan, Norizan (1998)
This study was conducted to determine the training needs of the officers in Direct Access in line with its mission to achieve the "best-in-class" quality service standards benchmarked against ISO 9000 standards. The main focus was to determine the degree of understanding of officers on the work processes as documented in the quality system of Direct Access as required under ISO 9002 and the level of importance to their work. Respondents selected for this study were all Deputy Manager, Assistant Managers, Senior Officers, Class A Officers and Class B Officers who were directly involved in the ISO 9002 process as documented in Direct Access's quality systems. A structured questionnaire based on the ISO 9002 standard was constructed and distributed to all respondents. Twelve out of nineteen elements of ISO 9002 covering the necessary work processes were included in the questionnaire. They were picked based on the relevance to the respondents' work as documented in the quality systems. Analysis on the information gathered were done using SPSS to get the frequencies, percentages, mean and standard deviation. The training need was determined by using the mean to identify the gap between the degree of understanding and the level of importance. A "gap index" was applied as the gap indicator. The training needs analysis indicated that majority of the respondents perceived all quality tasks according to the relevant elements of ISO 9002 presented in the questionnaire as of high importance to their work However. in terms of the degree of understanding, the findings revealed that most of the respondents did not have a good understanding of the work processes as required These work processes according to the ISO 9002 elements included Management Responsibility, Quality System, Contract Review, Document and Data Control, Product Identification and Traceability, Process Control, Control of Non-Conforming Products and Control of Quality Records.